Investigations into the Tectonic Faults on Magadi Geothermal Field Using Ground and Aeromagnetic Data - Komolafe, A.A. (2020)
Lake Magadi area of the Kenya Rift is characterized by faulting, tectonic activities and geothermal resources. The geothermal potential of the graben in the southern part of the lake was investigated using magnetic methods (ground and airborne). This was done to determine the geometry of tectonic faults and ascertain their influence on the flow of hot springs, which are manifested on the surface. Five N-S faults were identified for ground investigation using ground magnetic survey. Magnetic data were processed using vertical derivatives, analytical signal and Euler deconvolution. The faults were further mapped with aeromagnetic data using 2D Euler deconvolution. Magnetic derivative grids and profiles revealed subsurface faulting/tectonic activities up to a depth of 400m and the presence of fluid-filled zones within the basin, which are marked by the absence of magnetic sources. A deeper investigation into the lineaments from the aeromagnetic data showed that the surface faults extend to a depth of 7.5 km in the subsurface. The alignment of magnetic sources at the rift axis showed that these faults are probably the parallel faults which bound the basin/graben to the west and to the east. The N-S fault structures in the south of the lake serve as conduits for fluids which support the upward flow of the hydrothermal fluid along its margin.